2013
DOI: 10.1093/nar/gkt361
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of human Dicer-binding proteins TRBP and PACT in small RNA processing

Abstract: During RNA interference and related gene regulatory pathways, the endonuclease Dicer cleaves precursor RNA molecules to produce microRNAs (miRNAs) and short interfering RNAs (siRNAs). Human cells encode a single Dicer enzyme that can associate with two different double-stranded RNA (dsRNA)-binding proteins, protein activator of PKR (PACT) and trans-activation response RNA-binding protein (TRBP). However, the functional redundancy or differentiation of PACT and TRBP in miRNA and siRNA biogenesis is not well und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
155
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 28 publications
9
155
1
8
Order By: Relevance
“…The TRBP cofactor required by hDcr has been proposed to influence the cleavage site on pre-miRNAs that is utilized by hDcr (Lee and Doudna 2012;Lee et al 2013) and the Loqs-PB protein has also been proposed to influence pre-miRNA cleavage site selection by dDcr1 (Fukunaga et al 2012), resulting in the potential formation of alternative isomiRs. Moreover, the hDcr/TRBP complex has also been proposed to play a role in RISC loading (Chendrimada et al 2005;MacRae et al 2008).…”
Section: Synthetic Microrna Duplexes Efficiently Program Risc In Dicementioning
confidence: 99%
“…The TRBP cofactor required by hDcr has been proposed to influence the cleavage site on pre-miRNAs that is utilized by hDcr (Lee and Doudna 2012;Lee et al 2013) and the Loqs-PB protein has also been proposed to influence pre-miRNA cleavage site selection by dDcr1 (Fukunaga et al 2012), resulting in the potential formation of alternative isomiRs. Moreover, the hDcr/TRBP complex has also been proposed to play a role in RISC loading (Chendrimada et al 2005;MacRae et al 2008).…”
Section: Synthetic Microrna Duplexes Efficiently Program Risc In Dicementioning
confidence: 99%
“…Human Dicer also associates with two different dsRNA-binding proteins, TRBP and PACT (17,18). These dsRNA-binding proteins are not required for dicing activity but function as key regulatory factors in defining the dicing site and facilitating RISC formation (19)(20)(21).…”
mentioning
confidence: 99%
“…A second dsRBP, R2D2, cooperates with Dicer-2 to process exogenous siRNAs (reviewed in [38]). In mammals, two dsRBPs, TRBP and PACT, have been shown to interact with Dicer and modulate its substrate specificity [39].…”
Section: Other Components Of Micro and Sirna Biogenesismentioning
confidence: 99%
“…A second dsRBP, R2D2, cooperates with Dicer-2 to process exogenous siRNAs (reviewed in [38]). In mammals, two dsRBPs, TRBP and PACT, have been shown to interact with Dicer and modulate its substrate specificity [39].Alongside these biochemical studies, biophysical and structural efforts on dsRBPs have been successful in establishing the means by which the authentic dsRBDs recognize dsRNA [40]. In the case of the human dsRBP TRBP, structures of the first two dsRBDs domains, particularly the structure of the second domain bound to dsRNA, have shown that these RBDs exemplify the canonical dsRBD fold, binding the dsRNA through both major and minor groove interactions along the helical surfaces of the protein (Fig.…”
mentioning
confidence: 99%